Cardiotoxicity of Targeted Therapies in Children with Haematological Malignancies and Solid Tumors - Bangeas, Athanasios; Tragiannidis, Athanasios (Anti-Cancer Agents in Medicinal Chemistry, 2023)
Cardiotoxicity represents an important acute or chronic adverse event of treatment modalities for childhood cancer. In the last two decades the emergence of novel cancer therapies has aimed to increase unaided or mostly in combination with conventional chemotherapy for the survival rates of pediatric cancer especially for those patients with relapsed and/or refractory disease. The use of emerging targeted therapies in combination with conventional chemotherapy is related to cardiovascular adverse events mostly reported in adults. The aim of our short review was to investigate the cardiotoxic side effects of targeted chemotherapeutic agents as monoclonal antibodies and small molecules in pediatric cancer patients.
Keywords: children